Computational Analysis of Plasmodium falciparum Metabolism: Organizing Genomic Information to Facilitate Drug Discovery - Yeh, Iwei; Hanekamp, Theodor; Tsoka, Sophia; Karp, Peter D.; Altman, Russ B. (Genome Research, 2004)
Identification of novel targets for the development of more effective antimalarial drugs and vaccines is a primary goal of the Plasmodium genome project. However, deciding which gene products are ideal drug/vaccine targets remains a difficult task. Currently, a systematic disruption of every single gene in Plasmodium is technically challenging. Hence, we have developed a computational approach to prioritize potential targets. A pathway/genome database (PGDB) integrates pathway information with information about the complete genome of an organism. We have constructed PlasmoCyc, a PGDB for Plasmodium falciparum 3D7, using its annotated genomic sequence. In addition to the annotations provided in the genome database, we add 956 additional annotations to proteins annotated as “hypothetical” using the GeneQuiz annotation system. We apply a novel computational algorithm to PlasmoCyc to identify 216 “chokepoint enzymes.” All three clinically validated drug targets are chokepoint enzymes. A total of 87.5% of proposed drug targets with biological evidence in the literature are chokepoint reactions. Therefore, identifying chokepoint enzymes represents one systematic way to identify potential metabolic drug targets.